Frequency and forms of elder abuse in Serbia - Todorović Nataša; Vračević Milutin; Đikanović Bosiljka; Matejić Bojana (Temida, 2020)
This paper aims at presenting findings of the research that aimed at exploring the frequency of abuse targeting older persons, frequency of individual types of elder abuse, as well as the frequency of elder abuse targeting two different types of older persons. The research took place in 2016 in 9 Serbian municipalities and was designed as a cross-section study. It was conducted on a sample of 616 older persons of whom 58.1% (358) are socially less active and have some kind of support in daily life activities and 41.9% (258) are active in their communities and are socially included. The starting assumption of the research is that the frequency of elder abuse is more often in socially excluded persons than it is in socially included and more active ones. The research confirmed the correlation between the level of social activity and the risk of elder abuse and this correlation can be clearly explained by exploring other protective factors and risk factors such as income and education level or chronic diseases and disability.